Quality Of Live (QoL) Among People Living With Human Munodeficiency Virus (HIV) / Acquired Immune Deficiency Syndrome (AIDS): A Scoping Review Qualitative Research In Global Area - Trisyani, Yanny; Fajariyah, Nur; Darmayanti, Darmayanti; Hartutik, Sri; Indawati, Eli (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The increase in HIV cases is in line with the development of antiretroviral therapy (ART), which has an impact on increasing the life expectancy of HIV/AIDS patients. New challenges that accompany the increase in life expectancy of HIV/AIDS patients, namely how to ensure good quality of life (QoL) in patients. The methodology used in this Scoping Review adheres to the methodological guidelines outlined by Levac and Colquhoun. Cultural and cultural differences play a very important role in determining the quality of life in people with HIV/AIDS. A good understanding of the cultural context in a population can develop more effective interventions to address the challenges faced by people with HIV/AIDS as an effort to improve the quality of life in patients with HIV/AIDS Keywords: Quality of Life, Human Immunodeficiency Virus (Hiv), Acquired Immune Deficiency Syndrome (AIDS).  ABSTRAK Peningkatan kasus HIV tersebut sejalan dengan perkembangan terapi antiretroviral (ART), yang berdampak pada peningkatan angka harapan hidup pasien HIV/AIDS. Tantangan baru yang menyertai peningkatan harapan hidup pasien HIV/AIDS, yakni bagaimana memastikan kualitas hidup (Quality of Life/QoL) yang baik pada pasien. Metodologi yang digunakan dalam Scoping Riview ini mematuhi pedoman metodologis yang digariskan oleh Levac dan Colquhoun. Perbedaan kultur dan budaya memiliki peran yang sangat penting dalam menentukan kualitas hidup pada penderita HIV/AIDS. Pemahaman konteks budaya, yang baik pada suatu populasi dapat mengembangkan intervensi yang lebih efektif untuk mengatasi tantangan yang dihadapi oleh penderita HIV/AIDS sebagai upaya meningkatkan kualitas hidup pada pasien dengan HIV/AIDS. Kata Kunci: Kualitas Hidup, Human Immunodeficiency Virus (Hiv), Acquired Immune Deficiency Syndrome (AIDS).